Dissecting the Role of the Gut Microbiota and Diet on Visceral Fat Mass Accumulation (OR31-07-19). (13th June 2019) - Roy, Caroline Le; Bowyer, Ruth; Steves, Claire; Spector, Tim; Jordana, Bell
Abstract: Objectives: Accumulation of visceral fat mass (VFM) is a major risk factor for cardiovascular and metabolic disease. Both gut microbiota and diet have been shown to impact host adiposity in an interdependent manner, but the exact nature of their joint contributions has not been characterised. Here, we aimed to estimate and separate the effect of gut microbiota composition from that of nutrient intake on host VFM in of 1760 older female twins. Methods: The gut microbiome profile was assessed by 16S sequencing. VFM was measured by DEXA whole body scan and nutrient intake was assessed through food frequency questionnaires. We used a combination of pair-wise associations, random forest modelling and mediation analysis to separate the effect of the gut microbiota and nutrients on VFM. Results: Pairwise analyses revealed that 93 OTUs and 10 nutrients were significantly linked to VFM. Five of the 10 nutrients (fibre, trans fatty acids, magnesium, vitamin E and biotin) were also associated with 23% of the 93 VFM-associated OTUs. To separate the effects of the gut microbiota from nutrients on VFM we carried out conditional analyses. We observed that the majority (87%) of the 93 OTUs remained significantly associated with VFM irrespective of nutrient intake correction. In contrast, we observed that fibre, magnesium, biotin and vitamin E were no longer significantly associated with VFM when adjusting models for OTUs ( P  > 0.05), implying a role of the gut microbiota in mediating these nutrient effects on VFM. Formal mediation analysis revealed that the individual effect of fibre, biotin, magnesium and vitamin E on VFM were mediated at 69, 43, 41 and 31% respectively by OTUs. Moreover, we estimated that accumulated effect of OTUs on VFM (R2 = 0.19) was twice the one of nutrients (R2 = 0.11) and so were their prediction potential determined using random forest classification. Conclusions: Our results suggest that while the role of certain nutrients on VFM appears to depend on gut microbiota composition, specific gut microbes may affect host adiposity regardless of dietary intake. The findings imply that the gut microbiota may have a greater contribution towards shaping host adiposity and VFM, compared to diet alone. Funding Sources: We gratefully acknowledge support provided by the JPI HDHL funded DINAMIC consortium (administered by the MRC UK, MR/N030125/1). Supporting Tables, Images and/or Graphs: